2006
DOI: 10.1080/09674845.2006.11732735
|View full text |Cite
|
Sign up to set email alerts
|

Serum adiponectin levels and enzyme markers of liver dysfunction in diabetic and non-diabetic Caribbean subjects

Abstract: Low adiponectin levels are associated with elevated plasma alanine aminotransferase, a marker of reduced hepatic insulin sensitivity and a risk factor for type 2 diabetes. This study aims to determine the relationship between serum adiponectin level and alanine aminotransferase in diabetic and non-diabetic subjects. Fifty-six type 2 diabetic patients and 33 non-diabetic subjects participate in the study. Baseline plasma concentrations of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…The data showed that insulin levels decreased in GDM compare with those in the GC group, but significant difference was only observed in the GDM-N group. Several studies previously reported contradictory results regarding the regulation trend of insulin secretion in GDM when defects in β-cell function are present (22,23). In comparison with the GC group, the present study analysed the insulin levels in GDM-M and found no significant difference but, the GDM-M group revealed a negative correlation between maternal serum insulin level and HDL level.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The data showed that insulin levels decreased in GDM compare with those in the GC group, but significant difference was only observed in the GDM-N group. Several studies previously reported contradictory results regarding the regulation trend of insulin secretion in GDM when defects in β-cell function are present (22,23). In comparison with the GC group, the present study analysed the insulin levels in GDM-M and found no significant difference but, the GDM-M group revealed a negative correlation between maternal serum insulin level and HDL level.…”
Section: Discussioncontrasting
confidence: 65%
“…Studies have been performed either on non-pregnant subjects or on male subjects, which showed a negative correlation between ALT and adiponectin levels (45,46). In another previous study, which analysed serum adiponectin levels and enzyme markers of liver dysfunction in both type 2 diabetic and non-diabetic Caribbean non-pregnant women, it did not identify any significant correlation between adiponectin and ALT in either group of patients (22). In the present analysis, only in the GDM-N group did the adiponectin levels in the third trimester correlate positively with AST, whilst maternal serum levels of AST and ALT were not modified by the GDM status with or without macrosomia.…”
Section: Discussionmentioning
confidence: 99%